2006
DOI: 10.1007/s00125-006-0191-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and season-dependent differences in C-peptide levels at diagnosis of immune-mediated type 1 diabetes

Abstract: Aims/hypothesis: The incidence of type 1 diabetes varies according to age, sex and season of diagnosis. We investigated whether these and other clinical, biological and anthropometric parameters were correlated with residual beta cell function in newly diagnosed patients, since it is possible that the nature of external and/or genetic disease accelerators may be (partly) reflected in the inaugural disease presentation. Materials and methods: The correlates of random Cpeptide levels sampled shortly after diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…The same study showed that overweight or obese children with newly diagnosed T1D had a greater preservation of β‐cell function compared to lean children. Our work confirmed this correlation between random C‐peptide level and BMI SDS, as well as with age at diagnosis, suggesting that younger patients have lower C‐peptide levels at diagnosis and a more rapid decline in β‐cell function, reflecting the aggressiveness of T1D disease process in younger age . In 1998, Dorchy et al showed that the subgroup of diabetic children younger than 8 yr of age had lower C‐peptide level at diagnosis than the subgroup aged 8–14 yr .…”
Section: Discussionsupporting
confidence: 83%
“…The same study showed that overweight or obese children with newly diagnosed T1D had a greater preservation of β‐cell function compared to lean children. Our work confirmed this correlation between random C‐peptide level and BMI SDS, as well as with age at diagnosis, suggesting that younger patients have lower C‐peptide levels at diagnosis and a more rapid decline in β‐cell function, reflecting the aggressiveness of T1D disease process in younger age . In 1998, Dorchy et al showed that the subgroup of diabetic children younger than 8 yr of age had lower C‐peptide level at diagnosis than the subgroup aged 8–14 yr .…”
Section: Discussionsupporting
confidence: 83%
“…This may suggest that boys with autoimmunity are less likely to progress to overt disease than comparable girls and that the pathogenesis of T1D among boys may be slower compared with girls. Overall β-cell function may need to be further reduced in boys than in girls to progress to T1D (32,33). In addition, girls may have less insulin sensitivity owing to higher BMIZ than boys at the same age.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with childhood-onset type 1 diabetes, late-onset type 1 diabetic patients seem to have higher C-peptide values at diagnosis [38], disease progression is slower [39], and there are differences in epidemiological patterns [11]. It has been suggested that the environmental factors that trigger type 1 diabetes might be different in adult-onset disease [39].…”
Section: Discussionmentioning
confidence: 99%